2003
DOI: 10.3354/cr025029
|View full text |Cite
|
Sign up to set email alerts
|

Dry summers over northeastern South Africa and associated circulation anomalies

Abstract: Circulation anomalies associated with dry summers over northeastern South Africa are considered. Dry summers occurring during El Niño/Southern Oscillation (ENSO) episodes are examined separately from those during non-ENSO years, for which a greater mid-latitude influence on South African summer rainfall is evident. During the ENSO dry summers, anomalous upper tropospheric westerlies are dominant over most parts of the subcontinent and make the upper flow unfavourable for rain-bearing disturbances over northeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…The mean rainfall rate for DJF is 3 mm/day with a gradient from about 3.5 mm/day in the east to around 2.5 mm/day in the west. Anomalous wet and dry summers during this period agree with those derived by Mulenga et al (2003) for a slightly larger region of northern South Africa using monthly gridded data from the South African Weather Service. In addition, these authors showed that the region experienced significantly below average DJF rainfall for nine out of ten strong mature phase El Niño summers in the 1921-2001 period, with 1957/58 being the single exception.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…The mean rainfall rate for DJF is 3 mm/day with a gradient from about 3.5 mm/day in the east to around 2.5 mm/day in the west. Anomalous wet and dry summers during this period agree with those derived by Mulenga et al (2003) for a slightly larger region of northern South Africa using monthly gridded data from the South African Weather Service. In addition, these authors showed that the region experienced significantly below average DJF rainfall for nine out of ten strong mature phase El Niño summers in the 1921-2001 period, with 1957/58 being the single exception.…”
Section: Introductionsupporting
confidence: 75%
“…Figure 3). This increase in advection of South Atlantic air was identified by Mulenga et al (2003) as being a fundamental characteristic associated with anomalously dry seasons during neutral seasons as opposed to the El Niño-induced droughts where there is relative subsidence over southeastern Africa and an associated offshore shift of the tropical convection. In addition to the weakening of the South Atlantic anticyclone and increased advection of South Atlantic air, Figure 3 indicates that conditions are unfavourable for tropical-extratropical cloud bands to align themselves NW-SE across the country as is needed for good rains.…”
Section: Dry Spell Frequencies and Rainy Season Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither temperature nor pressure was significant in the amounts model. Although the ENSO indices were expected to be important based on the literature (Richard et al, 2000;Mulenga et al, 2003;Reason et al, 2005;Manatsa et al, 2008), none of these indices were within the eight most statistically significant external predictors.…”
Section: Spatial and Temporal Predictorsmentioning
confidence: 99%
“…During this time of the year, tropical weather systems invade southern Africa in the form of tropical cyclones, tropical lows and easterly waves (Karoly and Vincent, 1998). Also, wet spells during summer are pulsed at frequencies that are consistent with the passage of tropical waves over the southeast African and SWIO region (Hayashi and Golder, 1992) while anomalous easterly flow in the 5-20°S band in the region of Madagascar leads to increased rainfall over southeast Africa (Mulenga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%